Comparative Analysis of Narratives and Characterization in Jane Eyre and Madame Bovary - Jogthong, Chalermkwan (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2024)
This study examined the narrative structures and characterization in Charlotte Brontë’s Jane Eyre and Gustave Flaubert’s Madame Bovary. The objectives were to analyze the narrative technique, to analyze the characterization, and to compare the narrative techniques and characterization in the literature of Jane Eyre by Charlotte Brontë and Madame Bovary by Gustave Flaubert. Gérard Genette’s theories on narrative time and perspective formed the framework, which was then expanded upon. An examination was carried out on how the narrative perspectives in Jane Eyre and Madame Bovary impacted reader engagement with characters. Additionally, it explored how the settings influenced characters, referencing Tahir Woods’ concepts along with Mark Currie’s insights on narrative’s effects on readers’ perception of time. The research concluded with a discussion on how these novels depict character growth and human behavior complexities, underscoring the role of narrative techniques in reader immersion.